Hambatan Komunikasi dalam Upaya Pemasaran Hasil Budidaya Bioflok di Desa Lero Tatari - Yusaputra, Muhammad Isa; Antasari, Citra; Haidar, Nur; Fitrasari, Resky (Kinesik, 2024)
The results of research on communication barriers in marketing efforts for biofloc cultivation results in Lero Tatari Village, which can be seen from several types of obstacles, have not gone well. Technical obstacles, namely communication equipment in the form of cellphones, are affected by poor networks so that the message sent is different from the message received, and the marketing distance is quite far, changing the quality of the fish so that the agreed message changes. Semantic barriers are influenced by language differences that are poorly understood when marketing results, thereby hampering communication during the marketing process. Behavioral barriers where the communicator's behavior does not respond to the message conveyed by the communicant so that communication experiences obstacles during marketing and the attitude of the communicator who cannot control his emotions during the marketing process, namely the delivery of cultivated products far enough, resulting in a decrease in the quality of the fish resulting in misunderstandings with consumers which results in obstacles. communication.